Alone on an Island - Kingston, William Henry Giles, 1814-1880 (Salt Lake City, UT : Project Gutenberg, 2010)
"Alone on an Island" by William Henry Giles Kingston is a novel written during the Victorian era. Set in the midst of maritime adventures, the book largely revolves around themes of survival, faith, and personal growth as it tells the story of a young boy, Humphry Gurton, who finds himself stranded on a deserted island after a mutiny on the ship he serves. The narrative begins with Humphry$1 (Bs troubled life as he boards the privateer ship "Wolf" to escape his hardships, but soon he is caught in a chaotic mutiny where the crew takes control of the ship. Choosing to avoid the crew's dangerous lifestyle, Humphry opts for solitude on an uninhabited island. Throughout the story, he learns to adapt by fishing, gardening, and utilizing his surroundings to survive. His isolation transforms his character as he reflects on spirituality and ultimately leads to a profound friendship with a fellow shipmate, Ned Hadow, who unexpectedly appears on the island after learning from his own harrowing experiences. This novel captures not only the physical challenges of surviving alone in nature but also explores themes of redemption and the value of companionship. (This is an automatically generated summary.)s
Release date is 2010-11-29
Produced by Nick Hodson of London, England
Keywords: Sea stories; Conduct of life -- Juvenile fiction; Islands -- Juvenile fiction; Shipwrecks -- Juvenile fiction; Robinsonades